Optimize Security solution for mobile agent security: A Review (International Journal of Engineering and Computer Science, 2013)
The field of agents has many diverse researchers, approaches and ideas, which has helped to create one of the more dynamic research areas in recent years. Mobile agents are enjoying a lot of popularity and are destined to influence research in distributed systems for the years to come. Thus far, technology has been instrumental in disseminating new design paradigms where application components are not permanently bound to the hosts where they execute. Mobile agents are gaining in complexity as they evolve and are now widely used in e-commerce. All phases of a business transaction, such as negotiating and signing contracts can be done using mobile agents. In this paper, we provided a brief introduction to the recent researches & developments associated with the field of mobile agents, highlighting various security threats, also touching the weakest hot-spots of the field which need to be nurtured. This paper also focuses on the optimization of computation cost for agent platform, which appears due to complex security operations. Traditionally, a security manager is integrated within an agent platform, which performs these operations for every mobile agent visiting the platform. To reduce the security costs at the agent platform, a detached security manager is used, which performs complex security operations on behalf of multiple agent platforms. The paper is structured as follows. Section 1 Introduction to multi agent system and security. Section 2 briefly describes the characteristics of agents and Security Services. In section 3 we will discuss some security threats and countermeasures and in last section describes some recent research aimed at enhancing the security of mobile agent systems